2019
DOI: 10.3390/ijms20030632
|View full text |Cite
|
Sign up to set email alerts
|

Are the Biological and Biomechanical Properties of Meniscal Scaffolds Reflected in Clinical Practice? A Systematic Review of the Literature

Abstract: The aim of this PRISMA review was to assess whether the CMI and Actifit scaffolds, when used in clinical practice, improve clinical outcomes and demonstrate the ideal biological and biomechanical properties of scaffolds: being chondroprotective, porous, resorbable, able to mature and promote regeneration of tissue. This was done by only including studies that assessed clinical outcome and used a scale to assess both integrity of the scaffold and its effects on articular cartilage via MRI. A search was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…30 In addition, the rate of meniscal implant failure due to various reasons goes up to 31.8% according to the literature. 31 Therefore, our success rate was within the limits reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…30 In addition, the rate of meniscal implant failure due to various reasons goes up to 31.8% according to the literature. 31 Therefore, our success rate was within the limits reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…The collagen meniscal implant and Actifit scaffold were associated with good clinical outcomes, few complications (13%), and a low failure rate (6%) in 23 studies reviewed by Filardo et al, 47 although the studies in this review were of low quality. Furthermore, a meta-analysis by Houck et al 59 found no difference in the rate of treatment failure between the collagen meniscal implant and the Actifit (10% vs 7%; P > .05), and a systematic review by Ranmuthu et al 110 found some evidence that these 2 types of scaffolds were porous, mature, and resorbable and had possible chondroprotective effects as seen on MRI. A systematic review by Warth and Rodkey 138 examined outcomes of resorbable collagen meniscal implantation and generally found good clinical outcomes, minimal degenerative changes on postoperative radiographs, decreased signal intensity on MRI, the presence of meniscus-like tissue at second-look arthroscopy, and good integration of new tissue based on histological analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have evaluated scaffold implantations as alternatives to meniscectomy, with varied results. 40 Three studies looked at using these scaffolds as a substrate to bridge complex lesions or other lesions that are currently thought to be irreparable. [29][30][31] Utilizing biomaterials as adjuncts for meniscal repair is an attractive therapy as it potentially avoids the need for meniscectomy by providing a substrate for large or irregular lesions that are currently considered irreparable.…”
Section: Discussionmentioning
confidence: 99%